The relationship of home and instructional environments to L2 literacy development (Investigaciones) - Rendón Romero, Sara Isabel (2023)
Home and instructional learning environments can influence children’s literacy development in English as a Foreign Language. The main objectives of this research are 1) to determine the influence of school and home elements on children’s literacy process and 2) to identify reading practices and English tasks carried out at home. The research counted with the participation of 142 pupils and their families belonging to two different bilingual schools from Seville, Spain. This study followed an ex post facto design with natural groups in which quantitative data were collected through questionnaires to families and qualitative data through observations of pupils. Data were analysed through the Mann-Whitney U test and discriminant analysis. Results show that the frequency of reading in front of children, the mothers’ help with English tasks at home, and a certain amount of extramural English influenced the literacy process. Furthermore, the study identified significant differences between the two schools in relation to literacy practices at home and parental involvement in schoolwork. The results obtained present relevant implications in promoting family training and involvement and engaging in interactive collaborations with the school.